Relationship of Nitrogen Balance and Stroke Patient Recovery: A Systematic Review - Anshari, Zalfa Alya; Fuadiyah Nila Kurniasari; Fajar Ari Nugroho (Indonesian Journal of Human Nutrition, 2025)
Stroke is a major cerebrovascular disease and remains a leading cause of disability and mortality worldwide. Many stroke patients experience dysphagia and hypercatabolism, which contribute to negative nitrogen balance and may slow the recovery process. Urine Urea Nitrogen (UUN) offers an accurate representation of metabolic status than serum albumin, thus it can be used as a valuable indicator in nutritional evaluation and nutritional intervention strategies. This systematic review examines the relationship between nitrogen balance and recovery in stroke patients and assesses the effectiveness of UUN in evaluating nutritional status. Literature searches were conducted in Web of Science, Scopus, and PubMed databases for articles published between 2015 and 2025 using the keywords Nitrogen Balance, Protein Metabolism, Stroke, UUN, Rehabilitation, and Protein Intake. From 370 identified references, 14 studies met the inclusion criteria. Most studies used observational designs (64.29%) and were conducted in the United States (42.86%). A narrative thematic synthesis was applied to the included studies. The results consistently showed that negative nitrogen balance was associated with delayed neurological recovery and longer hospitalization, while higher protein intake improved nitrogen balance and rehabilitation outcomes. Urine Urea Nitrogen (UUN) was found to be a more accurate metabolic indicator than albumin levels for guiding nutritional interventions.